THE USE OF MULTIMODAL TEXT IN ENHANCING ENGINEERING STUDENTS’ READING SKILL - Cahyaningati, Desi Tri; Lestari, Lies Amin (International Journal of Language Education, 2018)
Abstract It is believed that the students’ low reading proficiency, as shown in their TOEIC scores, is due to their poor reading habit. One of the ways to overcome such a problem is by facilitating them with a lot of reading practices in an extensive reading program. Since today non-printed multimodal texts (NPMT) and Linear texts (LT) are available in the society, an experiment on which mode is most effective to enhance the students’ reading proficiency needs to be done. This study aims to investigate the effect of implementing non-printed multimodal text in an extensive reading program on the students’ reading comprehension. Two groups of students undertaking engineering major at a polytechnic in Surabaya, one group was exposed to NPMT and the other to LT in a one-semester extensive reading program, were chosen to be the subject of this quasi experimental study. A pretest and posttest on TOEIC were conducted to measure the students’ reading proficiency (only the reading scores of the test were analysed for the purpose of the study). The t-test analysis using SPPS for windows 23 shows that there is a significant difference in achievement between those who are exposed to NPMT and LT after the reading program ends (p-value = 0.010). The NPMT group gain better reading proficiency than that of the LT. It means the use of non-printed multimodal text in extensive reading can boost the students’ reading comprehension.